Foreign Language (FL) Teaching and Learning in Primary Schools in Europe: Beliefs and Realities - Kihlstedt, Maria (Emerging Trends in Education, 2019)
ince 2001, theCommon European Reference Framework for Languages(CEFR) is the main reference for teachers of foreign languages in Europe. However, difficulties of applying the CEFR and attaining the expected learning outcomes in the FL have been witnessed among teachers, especially as regards young learners. This paper aims at examining the underpinnings that lie behind the policy of foreign languages for young learners in the European Union. Focus will be on primary schools, starting ages and time of instruction. An illustration of the “unrealistic” expectations of learning outcomes with the CEFR will be given, considering empirical research evidence on learning a FL in preschool and primary schools. Some possible pedagogical solutions, such as CLIL (Content and Language Integrated Learning), teacher involvement and technology-mediated TBLT (Task-based Language Teaching) will also be discussed.